Energy Consumption and Economic Growth: Evidence from SADC Countries - Maune, Alexander; Matanda, Ephraim; Chitombo , Ezekiel (International Journal of Economics and Financial Issues, 2024)
This article examined the nexus between energy consumption and economic growth in selected Southern African Development Community countries for the period 1980 to 2015. The study used both simple and multiple linear regression models to examine the relationship between the variables. The statistical results of the simple linear regression model between energy use and economic growth show a correlation coefficient of 0.060. This represents a weak positive correlation between the model variables. A coefficient of determination of 0.00476 depicts that energy use explains only 0.476% of the variability in the gross domestic product of countries investigated. The multiple linear regression model results show a multiple R of 0.3684, and an R2 of 0.1358. This also depicts a weak positive correlation between the model variables. A coefficient of determination of 0.1358 means that energy use and electric power consumption accounts for only 13.58% of the values of the gross domestic product of selected Southern African Development Community countries and the balance is explained by the terms that are not specified in the model. This article is of value to policy makers in the region as well as the academia as it strives to close the gap in knowledge.